Preschool teachers' perceptions of STEAM-based learning in Banda Aceh - Gracia Mandira; Rahmi Sofyan; Khoiriyah Khoiriyah; Mutia Afnida; Wanbanyuree Kaweng; Putri Oktia Rezeki; Muhammad Usman (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
The purpose of this study was to identify early childhood teachers' perceptions of STEAM-based learning. This qualitative research will be analyzed descriptively, and semi-structured interviews with open-ended questions will be conducted with four early childhood education (ECE) teachers in Banda Aceh. The findings show that ECE teachers' perceptions of STEAM-based learning techniques have a high potential to be implemented in Banda Aceh City ECEs, as the respondents have used aspects of STEAM in their learning. Teachers' lack of knowledge of STEAM-based learning approaches and procurement of materials and funds to fulfil STEAM learning needs are barriers to integrating STEAM in ECE institutions in Banda Aceh. More STEAM socialization and STEAM learning implementation training is needed for ECE teachers in Aceh in general.